The Integrative Potential of Process in a Changing World: Introduction to a special issue on power, performativity and process. Issue 12 (December 2021) - Simpson, Barbara; Harding, Nancy; Fleming, Peter; Sergi, Viviane; Hussenot, Anthony
This editorial essay introduces a special issue that tackles the seemingly intractable challenge of re-conceptualizing power and performativity as continuously interweaving and co-emergent dynamics in the processes of organizing. It is in these processes, we argue, that new futures may be visibly made through the academic activism of our scholarly communities. We position our argument, and the six papers that comprise this special issue, in relation to Rosi Braidotti's framing of Humanism, anti-humanism and the posthuman. We also suggest some future lines of inquiry to move studies of organizing forward into a posthuman world.